Effect of inclined magnetic field on flow, heat and mass transfer of Williamson nanofluid over a stretching sheet - Srinivasulu, Thadakamalla; Goud, B. Shankar (Case studies in thermal engineering, 2021)
This research explores numerically the impact of the aligned magnetic field on Williamson's nanofluid on a stretching surface with convective boundary conditions. The ordinary differential equations (ODE's) are obtained from the partial differential equations (PDE's) employing the transformation of similarity. Such equations are computed with the respective limits with Runge-Kutta – Fehlberg's fourth-fifth order method along with a shooting procedure. The functions of the many parameter values on the flow field profiles are graphically presented and examined. The current results agree well with previous works. The local skin friction, the local Nusselt number, and the local Sherwood number are shown with graphs and tables for changed values of the flow constraints.